1993
DOI: 10.1121/1.407373
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency underwater sound generation by impacting transient cylindrical water jets

Abstract: The impact of a jet of water onto a still-water surface results in the entrainment of large amounts of air and the eventual formation of a bubble plume. Results from an experimental study of the noise produced by this process is presented. Preliminary results of this study were reported previously by Kolaini et al. [J. Acoust. Soc. Am. 89, 2452–2455 (1991)]. The densely populated bubble plumes were generated by dropping a fixed volume of water, held in a cylindrical container, onto a still-water surface. High-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…3 where multiple density lines exist inside the bubble and at the air-liquid surface. This matches the observation obtained from cinematography in the experiment of Kolaini et al, 12 which suggested that the "bubble plume" could be a large air-filled bubble with a roughened surface that contains air-water mixture.…”
Section: A Near-field Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…3 where multiple density lines exist inside the bubble and at the air-liquid surface. This matches the observation obtained from cinematography in the experiment of Kolaini et al, 12 which suggested that the "bubble plume" could be a large air-filled bubble with a roughened surface that contains air-water mixture.…”
Section: A Near-field Resultssupporting
confidence: 85%
“…Water surrounding the neck rushes radially toward the axis of symmetry, pinching off a large bubble plume. Detailed photographic images can be found in Kolaini et al 12 and ͑Szymczak et al͒. 31 The de- tached bubble plume undergoes volume pulsations, constituting a strong acoustic source radiating low-frequency sound.…”
Section: A Near-field Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is the impact of a continuous water mass, thus a liquid column or a jet, onto a pool (Kolaini et al 1993;Oguz, Prosperetti & Kolaini 1995;Clanet & Lasheras 1997;Storr & Behnia 1999;Kersten, Ohl & Prosperetti 2003;Szymczak, Means & Rogers 2004;Qu et al 2011). These studies focused on the bubbles resulting from the hydrostatic collapse of the generated cavity.…”
mentioning
confidence: 99%
“…Kolaini, Roy & Crum (1991) and Kolaini et al (1993) have experimentally considered the problem of a stationary short-duration water jet impacting on a quiescent pool of water. In these experiments, a vertically oriented tube of water was held in place above the pool, which was subsequently released by the sudden rupture of a rubber membrane, allowing a cylinder of water to impact with the pool.…”
Section: Introductionmentioning
confidence: 99%